Community partnerships (UK) vs Crime Prevention Councils (GER): Differences and similarities. (June 2016) - Frevel, Bernhard; Rogers, Colin
In the past two decades or so the way in which policing has been delivered to communities across Europe has changed. Previously, police agencies provided much of the public's security as a 'stand-alone' public body, with little or no interaction with other organisations. However, for a number of reasons explored in this article, police agencies across Europe have been engaged in building what has been termed a 'multi-agency' partnership, to aid their delivery of a wide range of police-type activities surrounding safety and security. This article considers the rise of such partnerships, focusing upon England & Wales (UK) and Germany. It further considers the context for the approaches adopted by both countries, and critically examines the differences and similarities between these approaches using the extensive individual research of the authors. Whilst acknowledging the difficulties associated with transnational research in general, the authors conclude that their use of similar research methods reveals some areas of close proximity in the approaches in each country, whilst acknowledging some areas of difference and under-development. Further research containing a planned and concrete research design, it is concluded, should provide for better understanding of the complexities of this kind of approach to policing in different countries.